2019
DOI: 10.1115/1.4042301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Upstream Exhaust Manifold on Pulsatile Turbocharger Turbine Performance

Abstract: This research was primary motivated by limited efforts to understand the effects of secondary flow and flow unsteadiness on the heat transfer and the performance of a turbocharger turbine subjected to pulsatile flow. In this study, we aimed to investigate the influence of exhaust manifold on the flow physics and the performance of its downstream components, including the effects on heat transfer, under engine-like pulsatile flow conditions. Based on the predicted results by detached eddy simulation (DES), qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Yang et al [44] linked the instantaneous absolute inflow angle to the time derivative of the ratio between static pressure and temperature, besides the geometric parameters of the volute. Lim et al [23] reported the exhaust manifold to have a direct effect on the inflow angle, as responsible for the secondary flows inside the volute.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al [44] linked the instantaneous absolute inflow angle to the time derivative of the ratio between static pressure and temperature, besides the geometric parameters of the volute. Lim et al [23] reported the exhaust manifold to have a direct effect on the inflow angle, as responsible for the secondary flows inside the volute.…”
Section: Resultsmentioning
confidence: 99%
“…1, consists of a single scroll and 12 blades turbine applied in a 2.0 L and four-cylinder engine passenger car. As the flow field inside the volute is largely affected by the system of the upstream bent pipes [23], the exhaust manifold is included in the model in order to replicate real on-engine conditions. Downstream to the turbine, the diffuser is followed by a convergent duct (not shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the flow thermal energy conversion ratios, the design of a heat exchanger was improved for better waste heat recovery [3]. In particular, many turbocharger studies focused on the utilization of energy carried by ICE pulsating flows, such as the impacts of different unsteady inlet conditions [4][5][6] along with reducing the thermal dissipation of exhaust pulses upstream of the turbine [7][8][9] and optimizing the configurations of turbocharging systems [10,11], to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the studies regarding time-varying flow parameters of exhaust pulsation, due to the challenges and limitations of on-engine time-resolved exhaust gas flow parameter measurement, assessment of instantaneous exhaust energy in literature often seeks assistance from simulations [6,17]. Apart from piezoresistive fast pressure sensors which are well established and widely used in ICE research [21], many previous studies attempted to capture the time-varying flow temperature and velocity (or mass flow rate) of exhaust pulsating flows.…”
Section: Literature Reviewmentioning
confidence: 99%